TARI JARANAN : SEBUAH PERMASALAHAN PENELITIAN SENI PERTUNJUKAN - Hidajat, Robby (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
<img src="data:image/png;base64,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